Building online facilitating skills in the new normal - Boholano, Helen B; Merin, Jewish A.; Dapat, Lelani C. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2021)
The sudden shift to remote teaching caused by COVID-19 pandemic has created a stressful and demanding context for teachers, specifically on the aspect of delivering remote instruction. This ascertained the challenges and opportunities encountered by 311 public basic education teachers attending different online training platforms and utilized the mixed method design in analyzing the data of the teachers’ online facilitation skills and used the scanning method in the data collection process. The challenges and opportunities they encountered was conducted through an unstructured interview via Zoom. The researcher-made questionnaires were sent to the teachers via email. Results revealed that teachers already had prerequisite ICT skills so the use of technology during the online training was not so much a threat in the enhancement of their ICT knowledge and skills except of the issues regarding very slow internet access and the lack of necessary and proper equipment and gadgets. In conclusion, teachers easily adopted to the shift from in-person to remote teaching; enhanced their ICT skills; and became prepared for remote teaching. Despite the sudden shift, these teachers remained positive in pursuing the direction for digital literacy to build an effective and efficient skills in remote teaching in the new normal.